Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21203/rs.3.rs-761501/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison study of percutaneous endoscopic interlaminar discectomy and transforaminal discectomy for L5-S1 calcified lumbar disc herniation

Abstract: Background: Percutaneous endoscopic lumbar discectomy (PELD) is a relatively safe and effective minimally invasive surgery in the treatment of calcified lumbar disc herniation (CLDH). However, studies on percutaneous endoscopic interlaminar discectomy (PEID) and percutaneous endoscopic transforaminal discectomy (PETD) for CLDH have rarely been reported. This research aimed to compare the clinical efficacy of PEID and PETD for L5-S1 CLDH.Methods: We retrospectively analyzed 54 consecutive patients with L5-S1 CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The operation time was available from 6 studies. [9–12,14,15] The heterogeneity was high ( I 2 = 96.42%). After sensitivity analysis of the study, it was found that Merter et al [14] was the source of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The operation time was available from 6 studies. [9–12,14,15] The heterogeneity was high ( I 2 = 96.42%). After sensitivity analysis of the study, it was found that Merter et al [14] was the source of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…The number of intraoperative fluoroscopy was available from 2 studies. [ 11 , 12 ] Analysis indicated that there was high heterogeneity among the studies ( I 2 = 0.00%) and fixed effect model was used. There are no significant difference (MD = 0.358, 95% CI [−0.097, 0.813], P = .123) between UBE and PELD group at the number of intraoperative fluoroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations